2007
DOI: 10.1300/j366v06n01_05
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Customer-Perceived Value, Satisfaction, Loyalty and Behavioral Intentions

Abstract: The concept of Customer-Perceived Value (CPV) has become a matter of increasing concern in marketing literature. However, there are few empirical studies that attempt to examine the notion of it. Filling this gap, this study provides a conceptual as well as empirical investigation of CPV as a formative construct and also offers an insight regarding the role of CPV in influencing, through satisfaction and loyalty, the behavioral intentions of word of mouth, repurchase intention and cross-buying. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 74 publications
3
91
1
5
Order By: Relevance
“…Given that it fundamentally consists of a collection of features relating to consumer perceptions of product value, the perceived value can be boosted via the effects of positive word-of-mouth and can, in turn, enhance consumers' purchase intentions [16,46]. Indeed, Gounaris et al (2007) [47] reported that consumer purchase intentions and perceived value are positively related; as such, a loss of purchase intentions may occur due to a low level of perceived value [35]. On the other hand, a consumer will be more likely to purchase a given product if the consumer perceives the value of the product to be high [40].…”
Section: Relationship Between Perceived Value and Purchase Intentionsmentioning
confidence: 99%
“…Given that it fundamentally consists of a collection of features relating to consumer perceptions of product value, the perceived value can be boosted via the effects of positive word-of-mouth and can, in turn, enhance consumers' purchase intentions [16,46]. Indeed, Gounaris et al (2007) [47] reported that consumer purchase intentions and perceived value are positively related; as such, a loss of purchase intentions may occur due to a low level of perceived value [35]. On the other hand, a consumer will be more likely to purchase a given product if the consumer perceives the value of the product to be high [40].…”
Section: Relationship Between Perceived Value and Purchase Intentionsmentioning
confidence: 99%
“…Loyalty and retention are many times associated and interconnected with the pursuit of satisfaction (Rahman, 2013). This linkage creates enormous costs, but based on the ndings of many studies brings low or even zero effect on the real retention (Blattberg, Getz, & Thomas, 2001;Malthouse & Mulhern, 2008;Carnegiea, Wilcoxb, & Zhuc, 2008;Gounaris, Tzempelikos, & Chatzipanagiotou, 2007). It is because satisfaction, described as the positive difference between expectations and delivered quality, is just one element of loyalty and retention.…”
Section: Customer Retention and Satisfaction Trapmentioning
confidence: 99%
“…C. Izquierdo et al (2006) in the study of Spanish bank clients divided the components of customer perceived value into three groups: (1) the functional dimension of value is created when the customer becomes aware of the financial services provider's advantages (brand credibility, quality of service, competence of the staff) and values them better than the services of their competitors; (2) the affective value occurs when the customer benefits from relations with the staff, emotional experience, self-identification with the brand and social integration; (3) the saving value is created after the customer perceives the offer as economically beneficial. Beside emotional value, social value, product value and experienced / perceived cost value some authors have also distinguished procedural value (perception of after-sales service and maintenance) and personnel value, which is created by professional skills and abilities of the service staff (Gounaris et al, 2007). Next to the functional and emotional attributes of value other authors studied rationale (customer's awareness of incurred cost) and risk (customer's uncertainty of the brand) attributes of value (Huber et al, 2007).…”
Section: Value As Multidimensional Conceptmentioning
confidence: 99%